Health research in humanitarian crises: an urgent global imperative - Brandon A Kohrt; Amit S Mistry; Nalini Anand; Blythe Beecroft; Iman Nuwayhid (BMJ Global Health)
Globally, humanitarian crises—such as armed conflict, forced displacement, natural disasters and major disease outbreaks—affect more people today than at any point in recorded history. These crises have immense acute and long-term health impacts on hundreds of millions of people, predominantly in low and middle-income countries (LMIC), yet the evidence base that informs how humanitarian organisations respond to them is weak. Humanitarian crises are often treated as an outlier in global health. However, they are an increasingly common and widespread driver of health that should be integrated into comprehensive approaches and strategies, especially if we hope to achieve ambitious global health targets such as the Sustainable Development Goals. The academic research community can play an important role in addressing the evidence gap in humanitarian health. There are important scientific questions of high public health relevance that can only be addressed by conducting research in humanitarian settings. While working in these settings is uniquely challenging, there are effective strategies that can be employed, such as using flexible and adaptive research methodologies, partnering with non-governmental organisations and other humanitarian actors, and devoting greater attention to issues of research ethics, community engagement, local LMIC-based partners, building humanitarian research capacity and collaborating across disciplines.